HUMANIST-SPIRITUAL LEADERSHIP AS A STRATEGY TO BRIDGE THE GAP IN TEACHER COMPETENCE IN MADRASAH EDUCATION - Shomitah, Luluk; Na'imah, Na'imah; Sa'adah, Mifthahus; Ariyani, Ika Tiara; Jabil, Cici Laras (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Strengthening teacher competence is the main pillar of improving the quality of madrasah education. At MTs TQ El-Muna Q, 73% of teachers have non-pedagogical backgrounds, which creates inequality in teaching skills and leads to monotonous teaching methods. This qualitative case study aims to analyze the role of the Humanist-Spiritual Madrasah Head's leadership in overcoming these challenges. Data was collected through interviews, observations, and documentation involving the Head of Madrasah, Waka Curriculum, and two teachers. The results of the study show that the leadership of the Head of the Madrasah applies the Spiritual-Transformational principle by integrating the humanist dimensions (empathy and appreciation) and the spiritual (value of worship and trust). This model has been shown to foster intrinsic motivation and bridge the skill gap through personalized coaching and constructive supervision. While it can improve learning quality, its sustainability is hampered by administrative burdens and time constraints, underscoring the need for managerial efficiency to protect teachers' focus on their core tasks. This research contributes to Islamic educational leadership theory by proposing a humanist-spiritual leadership model as an effective mechanism to bridge pedagogical gaps through value-based coaching, constructive supervision, and strengthening intrinsic motivation in faith-based educational institutions.